1990
DOI: 10.1080/00029157.1990.10402899
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic Susceptibility and Experimental Pain Reduction

Abstract: We exposed 24 subjects high in hypnotic susceptibility and 24 subjects low in hypnotic susceptibility to a cold-pressor pain stimulus under either hypnotic or waking conditions, using each of two pain-reduction strategies (analgesia and distraction) separately. Trance depth level was held constant for hypnotized subjects. We used pain-tolerance levels as measures of pain, and we analyzed them by survival analysis. High susceptibles reported significantly lower pain ratings and kept their hands immersed longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These earlier studies showed that each of our hypnotic and nonhypnotic analogue treatments were more effective than a no-treatment control condition in reducing pain, but there was no difference between the treatments. Similarly, several other investigators failed to detect a difference between hypnotic analgesia and simple (Spanos et al, 1984;Tenenbaum, Kurtz and Bienias, 1990) or Stress Inoculation Training (Miller and Bowers, 1993;Spanos, Ollerhead andGwynn, 1985-1986) in reducing cold pressor pain. However, none of these past studies utilized a placebo control condition.…”
Section: Discussionmentioning
confidence: 97%
“…These earlier studies showed that each of our hypnotic and nonhypnotic analogue treatments were more effective than a no-treatment control condition in reducing pain, but there was no difference between the treatments. Similarly, several other investigators failed to detect a difference between hypnotic analgesia and simple (Spanos et al, 1984;Tenenbaum, Kurtz and Bienias, 1990) or Stress Inoculation Training (Miller and Bowers, 1993;Spanos, Ollerhead andGwynn, 1985-1986) in reducing cold pressor pain. However, none of these past studies utilized a placebo control condition.…”
Section: Discussionmentioning
confidence: 97%
“…Not surprisingly, the literature on analogue studies of pain indicates that highly hypnotizable patients show the greatest reductions in pain (Bowers & LeBaron, 1986;Hilgard, 1980). However, this relationship has not been found to be as clear in the clinical pain literature (Gillett & Coe, 1984;Tenenbaum, Kurtz, & Bienias, 1990). Because patients who score low on hypnotizability scales also benefit from hypnosis (Chaves, 1993), the relationship between hypnotizability and analgesia is not likely a linear one.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, increasing evidence shows that suggestions modulate pain experience both in and out of hypnosis [6], [7], [8], [18], [24], [25]. Thus, the aim of the present study was to investigate the psychophysical, respiratory and autonomic correlates of pain modulation induced by non-hypnotic suggestions of analgesia in highs and lows undergoing cold pressor test.…”
Section: Introductionmentioning
confidence: 92%